(untitled) (Heritage, 2025)
The author of this paper focuses on a hitherto insufficiently researched element of the cultural heritage of Serbs in Kosovo and Metohija related to posthumous customary and ritual practices. It’s about placing large wood-carved crosses on the grave of the deceased for the forty-day commemoration, which is a practice that, historically speaking, was recorded more widely among Serbs in Kosovo and Metohija, but also in central Serbia. When it comes to the southern Serbian province, that practice till today has been preserved only in the territory of the Leposavić municipality, which is why it can be said that in the modern, current moment, it represents a cultural heritage specific to the Serbian population in the aforementioned area. Based on the analysis of the main features of the studied phenomenon, the conclusion of the research is that in the perception of the bearers of the observed cultural heritage – Serbs in the area of the Leposavić municipality – the placing of large wooden crosses on the grave of the deceased symbolizes the act of sending a gift to the deceased by family members and closest relatives, which is the way to express grief for the deceased on the forty-day commemoration, but also to send him/her a final greeting, farewell, and the like. According to the structural elements it contains, the researched segment of the cult of the dead among Serbs in the area of the Leposavić municipality belongs primarily to folk tradition, while the wood-carved grave crosses themselves, or krstače, as these grave markers are most often called in the speech of local Serbs, can be included in the group of crosses that Veselin Čajkanović calls the common Serbian cross or simply the folk cross.